Survival of transport-stressed black pepper stem cuttings after glucose, sucrose, fructose, and IBA treatments - Zakry, Fitri Ab Aziz; Idris, Nur Natasya Ilyanis; Sazili, Muhammad Iqbal Nul Hakim Mohd; Kundat, Franklin Ragai; Saupi, Noorasmah; Bokhari, Semsolbahri (Journal of Phytology, 2025)
This study aimed to determine the survival, sprouting, and rooting performance of black pepper stem cuttings to glucose, sucrose, and fructose at different concentrations. The two-node stem cuttings were prepared from six to seven-node cuttings collected from mother vines of black pepper in the field from far and remote areas in Sarawak, Malaysia. The two-node cuttings were soaked completely for one hour with the following treatments: 1% glucose, 2% glucose, 3% glucose, 1% sucrose, 2% sucrose, 3% sucrose, 1% fructose, 2% fructose, 3% fructose, and 1000 ppm IBA served as a positive control, while filtered water was a negative control. All treated cuttings were sown in the polybags containing soil mix and monitored daily for up to 45 days. The study found that black pepper cuttings treated with a 3% glucose solution exhibited significantly better survival, sprouting, and rooting, total number of roots, and total length of roots at day 45, but they were about the same when soaked in IBA at 1000 ppm. The present study demonstrates that cuttings that have been in transit for a long time require sugar and hormone treatment once they arrive at a certain location to restore their vitality and survival.